Kontrol Diri dan Perilaku Phubbing Dilingkungan Siswa - Wenny Audina Kartikasari; Firman Firman; Afdal Afdal (Institut Agama Islam Negeri Kerinci, Indonesia, 2023)
Smartphones are a form of technology that is becoming an everyday necessity for all individuals across all age groups, and phubbing stands for phone snubbing, defined as the behavior of ignoring other people during social interactions and instead focusing on the phone. This study aims to see how problematic smartphone use can trigger phubbing behavior caused by a lack of self-control so that it can increase phubbing behavior. This research method uses a type of library research that contains reviews, summaries, and thoughts on phubbing problems in students at school, which aims to reveal various theories relevant to the problems being faced as material for discussion of research findings. The results of this study reveal a relationship between the level of self-control and phubbing behavior, meaning that students with a higher level of self-control tend to exhibit lower phubbing behavior. Further research is likely to examine the relationship between self-control and phubbing behavior in students at school